Why Should We Worry About Sea Level Change? - Siegert,MJ (Frontiers for Young Minds, 2017)
Around 250 million people live by the coast, less than 5 m above the sea. Changes in sea level affect people through flooding, when water in rivers cannot flow into the ocean because the sea is too high and when seawater surges onto the land during storms. If the sea water finds its way to farms and reservoirs, it can harm our drinking water and our ability to grow crops. Because of this, knowledge of how and why sea level is changing is of importance to society.